Tomada de decisão por gênero: um olhar sobre homens e mulheres em posição de alta gestão - Costa, Lilian Cidreira da (2014)
Strategic decision-making is a theme used over the years to help men and women, particularly in organizations, to think in a structured way on how to decide, which arguments and how to adopt them. With the entry of women into the labor market, the decision-making theory has expanded to analyze not only the decision-making process itself, but also behaviors used by men and women in these moments. The aim of this study was to investigate the theories of gender decision-making and verify if these theories are related to the reality of men and women who are in top management positions and, on this basis, analyze if the theories are confirmed when men and women are in top management positions. Moreover, we also sought to investigate whether the theory of empowerment has something to do with the theories of decision-making taken by gender, as well as the empowerment levei delivered to managers and directors in organizations influence the decision-making characteristics used for these men and women. For this purpose, a semi-structured survey was used for twenty-four professionals in management positions and board positions in companies based on the state of Rio de Janeiro. As a result, the research concluded that the way men and women make strategic decisions in organizations unrelated to the gender decision-making theories when they are in management and board positions, however, the way men and women of high management decide has an intimate relationship with the empowerment leve] that they have within companies that act.